DEVELOPING CRITICAL THINKING SKILLS THROUGH MICROTEACHING - Ika Wahyuni Lestari (Universitas Islam Negeri Alauddin Makassar, 2019)
This study aimed to explore how microteaching improved the students’ critical thinking skills. The method used was qualitative research. The procedure of collecting the data was assigning 20-minute microteaching to nine groups of preservice teachers over nine weeks of teaching and learning process. In a group of two to three, they were asked to demonstrate their understanding on how to teach English to young learners based on a given topic. Peer feedback and teacher feedback were also given as a post-activity. Two preservice teachers were interviewed to explore their views on how the microteaching model influenced their critical thinking. The results showed that all stages of the microteaching model - the preparation and planning, the 20 minutes microteaching, peer feedback, and teacher feedback - enhanced their critical thinking skills.